A workplace mindfulness training program may affect mindfulness, well-being, health literacy and work performance of upper-level ICT-managers: An exploratory study in times of the COVID-19 pandemic - Schubin, Kristina; Seinsche, Laura; Pfaff, Holger; Zeike, Sabrina (Frontiers in Psychology, 2023)
Mindfulness-based interventions have gained more importance in workplace health promotion due to increased psychological distress in the digital era. Although managers in the ICT-sector are at risk for lower mental health, few studies have evaluated the effects of workplace mindfulness trainings (WMT) on upper-level ICT-managers. By applying a mixed methods approach, the study aimed at exploring differences in upper-level ICT-managers’ mindfulness, well-being, health literacy and work performance at the beginning of a WMT (t0), immediately after (t1) and three months after (t2) a WMT. Thirteen groups of managers (n = 56) completed the training and three corresponding surveys consecutively from October 2019 to April 2021. Managers rated their mindfulness (MAAS), well-being (WHO-5), health literacy, and work performance (HPQ). During the COVID-19-pandemic the training switched from a live on-site mode to a hybrid mode and finally to a digital mode. Repeated measures ANOVAs and Bonferroni-adjusted post-hoc analyses were used for data analysis. Open-ended responses were content analyzed. We found significant differences in managers’ mindfulness (F (2.106) = 3.376, p = .038, ηp2 = .06, n = 54), well-being (F (2.106) = 73.019, p < .001, ηp2 = .17, n = 54), health literacy (F (2.108) = 9.067, p < .001, ηp2 = .15, n = 55), and work performance (F (2.80) = 7.008, p = 0.002, ηp2 = 0.15, n = 41) between t0 and t2. Significant differences between t0 and t1 were also found for well-being, health literacy and work performance, but not for mindfulness. Qualitative findings demonstrated positive training effects, barriers and facilitators to daily application of mindfulness practice. The results suggest that compared to beginning of the WMT, the post and follow-up measurements showed outcome improvements. The workplace mindfulness training may thus be a promising program to facilitate mental health and working capabilities among upper-level ICT-managers. Contextual workplace factors need to be considered to sustain long-term mindfulness practice of managers.